Differential Regulation of Myeloid-Derived Suppressor Cells by Candida Species - Singh, Anurag; Lelis, Felipe; Braig, Stefanie; Schäfer, Iris; Hartl, Dominik; Rieber, Nikolaus (Frontiers in Microbiology, 2016)
Myeloid-derived suppressor cells (MDSCs) are innate immune cells characterized by their ability to suppress T-cell responses. Recently, we demonstrated that the human-pathogenic fungi Candida albicans and Aspergillus fumigatus induced a distinct subset of neutrophilic MDSCs. To dissect Candida-mediated MDSC induction in more depth, we studied the relative efficacy of different pathogenic non-albicans Candida species to induce and functionally modulate neutrophilic MDSCs, including C. glabrata, C. parapsilosis, C. dubliniensis and C. krusei. Our data demonstrate that the extent of MDSC generation is largely dependent on the Candida species with MDSCs induced by C. krusei and C. glabrata showing a higher suppressive activity compared to MDSCs induced by C. albicans. In summary, these studies show that fungal MDSC induction is differentially regulated at the species level and differentially affects effector T-cell responses.